Pengurangan Kecurangan Garansi melalui Kebijakan Inspeksi dan Garansi Kombinasi pada Baterai Mobil - Alfiah Fajri, Asri; Iskandar, Bermawi Priyatna (Journal of Research in Industrial Engineering and Management, 2024)
Warranty plays a crucial role in marketing new products as they signal the quality of the product to consumers. However, implementing warranty also requires warranty providers to incur additional costs known as warranty costs. The annual warranty costs for global automotive manufacturers have increased from 2018 to 2022, with fraudulent warranty claims estimated to account for 3-15% of the total warranty costs. This study aims to develop an effective decision model to minimize warranty fraud on batteries for cars produced by PT. X. Car battery warranty claim data from 2019, recorded and inspected by PT. X, was used to develop a failure model, warranty policy models, and decision-making model using Nash game theory. The findings indicate that the Pro-Rata Warranty (PRW) policy is more effective in reducing warranty fraud. The results also suggest that customer behavior in committing fraud is influenced by several factors, including product reliability, penalty costs, inspection costs, battery manufacturing costs, battery purchase costs, and the period of Free Replacement Warranty (FRW) policy. Optimal inspection strategies and appropriate warranty policies can significantly reduce warranty fraud, thereby reducing the warranty cost burden borne by the warranty provider.